1964
DOI: 10.1039/jr9640003062
|View full text |Cite
|
Sign up to set email alerts
|

586. Photochemical cyclisation of diels–alder adducts

Abstract: endo-Adducts of cyclopenta-or cyclohexa-1, 3-dienes with cyclohexa-1,4-dienes, especially p-benzoquinones (Ia) , cyclise on ultraviolet irradiation to cage-like isomers (Ib) by formation of a cyclobutane ring from the two double bonds. The effects of interaction between the two carbonyl groups in the photoisomers (Ib) appear in their infrared and ultraviolet spectra. * After the appearance of our preliminary note 3 we learnt €hat the photoisomerisation of benzoquinone adducts had been independently observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
105
0
6

Year Published

1980
1980
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(112 citation statements)
references
References 0 publications
1
105
0
6
Order By: Relevance
“…It was initially assigned the endo-syn-endo structure 12 (13,14), but was later proved to be the endo-antiendo isomer 13 (1 1, 15, 16), as confirmed by X-ray crystallography (10). A second stereoisomer, mp 186"C, was prepared by isomerization of 13 with alkali, and was assigned the endosyn-exo structure 14 (15,16). Very recently the synthesis of a third stereoisomer, mp 184"C, was reported; this is assigned the endo-syn-endo structure 12 on the basis of its method of preparation and its reactions (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was initially assigned the endo-syn-endo structure 12 (13,14), but was later proved to be the endo-antiendo isomer 13 (1 1, 15, 16), as confirmed by X-ray crystallography (10). A second stereoisomer, mp 186"C, was prepared by isomerization of 13 with alkali, and was assigned the endosyn-exo structure 14 (15,16). Very recently the synthesis of a third stereoisomer, mp 184"C, was reported; this is assigned the endo-syn-endo structure 12 on the basis of its method of preparation and its reactions (17).…”
mentioning
confidence: 99%
“…Tetrahydro 2:l adducts Hydrogenation of the original 2: 1 adduct 13 gives a tetrahydro compound 23, mp 255°C; similar treatment of the isomer 1 4 gives a tetrahydro compound 24, mp 188°C (13,15,16). Compound 24 could also be obtained by alkaline treatment of 23 in :he same fashion that 13 was converted to 14, or by heating 23 above its melting point (ca.…”
mentioning
confidence: 99%
“…The equilibrium 12 13 evidently lies far to the right (no C=O bond in ir spectrum). By contrast, Cookson et al (4) found that treatment of 1 with one mol (4 equivalents) of sodium borohydride gave a mixture of mono-and di-reduction products, and that the former existed mainly as uncyclized hydroxy ketone (C=O in ir). Treatment of 1 with a large excess of borohydride gave a mixture of isomeric diols.…”
Section: "Ohmentioning
confidence: 99%
“…gave the ether 14 as the only product, even after The attempt to obtain bishomohypostrophene prolonged standing. Recently Nakazaki et al (1 1) from the homologous diketone 9 (4,8,9) by a simi-converted 10 into 14 by treatment with sulfuric acid lar series of reactions failed. Lithium aluminum in acetic acid at 120°C for 42 h. Evidently polyhyhydride reduction of 9 gave a diol(10, 11) for which drogen fluoride -pyridine may prove advantageous Dekker et al (10) have established the endo,endo in the conversion of some diols into ethers under configuration (10) by reaction with thionyl chloride mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The excellent overall yields of dilactones 5 and 8 from such readily available precursors render these compounds highly accessible synthons for all- (1,6) although apparently only two of these have been reduced to their dihydro derivatives (3,4). Thus, a considerable scope of synthetic utility is predictable for this sequence.…”
mentioning
confidence: 99%